Relationship between Speed and Leg Muscle Strength with the Long Jump Squat Style Results in Class VIII Students at SMP Negeri 1 Penuguan - Al Jawani, Luthfi Ma’ruf; Lian, Bukman; Hermansah, Bambang (Journal of Social Work and Science Education, 2023)
The purpose of this study was to determine the relationship between speed and leg muscle strength with the long jump squat style in class VIII students at SMP Negeri 16 Palembang. The method used is multiple correlation. Test variables x1 (speed), x2 (leg muscular strength), and Y (outcome of long jump squat style) are used in research data gathering methodologies. Hypothesis testing findings demonstrate a link between leg speed and muscular strength and the results of the squat style long jump in class VIII students at SMP Negeri 1 Selat Penuguan. According to the testing hypothesis, there is a link between speed and the results of long jump squat style. Second, there is a link between leg muscular strength and the outcomes of the squat-style long jump. Third, with the long jump squat method, there is a link between speed and leg muscular strength. The F-test results are then computed, and F table, this study concludes that Ha is accepted when F count (7.815) > F table (2.87). This suggests that there is a link between speed and leg muscular strength and the outcomes of the squat style long jump in SMP Negeri 1 Selat Penuguan class VIII students.